Assessment of Portal Vein Thrombosis in Cirrhotic Liver Patients - Muhammad Aslam Rind, Fida Hussain, Maria Nazir, Saleem Rind (Pakistan Journal of Medical & Health Sciences, 2024)
Background: PVT has a number of frequent causes, including cirrhosis of the liver, abdominal inflammation, tumour invasion, and thrombophilic disorders. Aim: To find out how frequently liver cirrhosis patients get portal vein thrombosis. Study Design: Cross-sectional study, Department of Medicine, Liaquat University Hospital Hyderabad, Sindh, Pakistan's from 1st April 2021 to 30th September 2021.One hundred and twenty eight patients were enrolled. The demographic information like age, sex, and body mass index were noted. Hepatocellular carcinoma patients and history of thromboembolism propensity were excluded. Both male and female patients with hepatic cirrhosis and age ranged from 20 to 50 were included. The monitoring of portal vein thrombosis, Doppler ultrasonography was performed on all patients. Results: There were 40(34.4%) female patients and 84(65.6%) male patients with average age was 51.95 7.54 years and BMI was 31.87 2.64 kg/m2. Seventy nine patients (61.7%) had hepatitis C, 50 patients (39.3%) had hepatitis B, 66 patients (51.6%) had diabetes mellitus, 81 patients (63.3%) had hyperlipidaemia, and 69 patients (57.9%) had hypertension. The prevalence of portal vein thrombosis (PVT) was 81(63.3%), with 48(59.3%) of the cases involving men and 33 (40.7%) involving females. Of them, 25 patients (50%) had hepatitis B and 44 (55.7%) had hepatitis C. Conclusion: Patients with liver cirrhosis experienced portal vein thrombosis often, and hepatitis C patients made up the majority of those afflicted. Keywords: Thrombosis, Portal vein, Liver cirrhosis, thrombophilic disorders